Countdown to True Wireless Broadband - Imran Edzereiq, Kamarudin (Faculty of Computer Systems and Software Engineering, 2011)
Mobile internet has become common in Malaysia, but the current generation of 2G and 2.5G hardly classify as broadband. While 3G and 3.5G technologies do mark as beginning, the upcoming 4G technologies namely 802.16m WIMAX (Worldwide Interoperability for Microwave Access) and LTE (3GPP Long Term Evolution) release 10 – are truly broadband wireless access (BWA). BWA is the evolution of 20 years plus of mo-bile technology, starting from first generation communication or 1G which purely on voice without broadband data then comes 2G with Global Packet Radio Service (GPRS) and Enhanced Data rates for GSM Evolution (EDGE) as the basic of data service offering.